Structure-based pharmacophore design and screening for potential inhibitors of E protein of dengue virus as a loom for dengue - Indu Purushothaman, Girija Saravanan, Aruna Sundararajan, Meena Karunaguran Sulochana (Journal of Applied Pharmaceutical Science, 2019)
Dengue virus (DENV) poses a continuous threat worldwide with an estimated 2.5 billion people at the risk of dengue infection. It was believed to be the infection of the tropical regions, but reports of dengue infection have now extended and spread around the globe. The dengue E protein is involved in the viral fusion and could thus acts a potential target against dengue virus. In the present study, structure-based pharmacophore design and screening and absorption, distribution, metabolism, excretion, and toxicity (ADMET) analysis using Discovery studio (4.0) was applied to identify potential hits against the hydrophobic pocket of dengue E protein. The pharmacophore feature of screened compounds was further validated and finally three lead compounds were obtained. The pharmacophore model and the docking study were generated three lead molecules Ophiopoginin D with a binding energy of −146.36 Kcal/ mol followed by Calmisttrin D with a binding energy of −118.73 Kcal/mol and BTB 08305 with a binding energy of −99.96 Kcal/mol and exhibited best-fit value. ADMET profile showed that all the three lead molecules are non-toxic, non-carcinogenic, and non-hepatotoxic by in silico study. The compound Calmisttrin D exhibited good blood brain barrier permeability and human intestinal adsorption, and thus hypothesized to have antiviral activity against dengue virus and so further in vitro and in vivo evaluation is recommended.
Keywords: Dengue virus, pharmacophore feature, E protein, Calmisttrin D.